2017
DOI: 10.1007/s00414-017-1533-6
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of medical reports in criminal investigations of cases of suspected child abuse

Abstract: If a case of physical child abuse is suspected in Germany, the general feeling is often that "it does not matter whether you make a report or not" because, generally, no conviction is made anyway. This study investigates the juridical analysis of complaint cases of physical child abuse [criminal complaint parag. 225 StGB (German penal code) with filial victim]. It focuses on the doctor's role and the impact of their practice in relation to a later conviction. It is based on the analysis of 302 files of the enq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…For example, a study conducted in Hungary from 2000 to 2015 reported that 48% ( n = 205) of the 426 child sexual abuse cases reviewed had legal proceedings with only 9.6% of perpetrators ( n = 41) receiving judgments from the court (16). The closest comparable information to the current study took place in Germany which operates under a civil law system, and, as such, is not comparable to the common law system predominantly used in America (17). As Syam explains, “The main difference between the two systems is that in common law countries, case law—in the form of published judicial opinions—is of primary importance, whereas in civil law systems, codified statutes predominate” (18).…”
Section: Objectivesmentioning
confidence: 52%
“…For example, a study conducted in Hungary from 2000 to 2015 reported that 48% ( n = 205) of the 426 child sexual abuse cases reviewed had legal proceedings with only 9.6% of perpetrators ( n = 41) receiving judgments from the court (16). The closest comparable information to the current study took place in Germany which operates under a civil law system, and, as such, is not comparable to the common law system predominantly used in America (17). As Syam explains, “The main difference between the two systems is that in common law countries, case law—in the form of published judicial opinions—is of primary importance, whereas in civil law systems, codified statutes predominate” (18).…”
Section: Objectivesmentioning
confidence: 52%
“…Apesar de os profissionais de saúde desempenharem importante papel na rede de proteção da criança e no manejo dos casos de violência (12)(13) , e de os direitos ligados à infância e à juventude estarem expressos em constituições e declarações nacionais (4,7) e internacionais (14) , a universalização da garantia desses direitos ainda é um desafio atual (5) .…”
Section: Introductionunclassified